2020
DOI: 10.1016/j.sjbs.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The first bioactivity studies of Acantholimon lycopodioides from high altitude Karakoram-Himalayan desert

Abstract: Couple of ethnopharmacological surveys in the Indian Ladakh and Pakistani Shigar valleys has reported the medicinal use of Acantholimon lycopodioides against cardiac and gastric disorders that however, remains without scientific rationale or experimental validations. Here, we assess the in vitro bio/therapeutic activities of A. lycopodioides extracts as well as chloroform, ethyl acetate, n-butanol and aqueous fractions. The in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The genus contains many plants as endemic species [6,10]. Extracts of this plant species are known to exhibit very good inhibitory effects on a wide variety of bacteria, fungi, and different cell lines [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus contains many plants as endemic species [6,10]. Extracts of this plant species are known to exhibit very good inhibitory effects on a wide variety of bacteria, fungi, and different cell lines [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported to have a medically traditional use among people in Asia [22,23]. The biological activities of extracts and some fractions of the species Acantholimon lycopodioides were studied by [24]. In the study, they reported that Acantholimon species have important biological activities in terms of antimicrobial, antioxidant, anticancer, and hepatoprotective properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation